Building intellectual bridges and shared agendas / Strategy and example: gender in agricultural research as a driver for inclusive transformation - Curnow, Jayne; Wilde, Vicky (Australian Centre for International Agricultural Research, 2019)
Presented by Jayne Curnow (Australian Centre for International Agricultural Research) and Vicki Wilde (Bill & Melinda Gates Foundation), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.